Performance Evaluation of Teachers and Educational Staff as a Tool for Improving the Quality of Education - Abdul Hamid; Siti Aimah (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
This study aims to analyze how the performance evaluation of educators and educational staff serves as a strategic tool in improving the quality of education by strengthening professionalism, enhancing the effectiveness of task performance, and continuously improving the quality of educational services. This study employs a qualitative approach using a case study design conducted at Muadalah Wustho Darussalam in Blokagung, Banyuwangi, over the course of one month. The study involved four informants selected through purposive sampling, consisting of the head of the institution, two educators, and one educational staff member. Data were collected through observation, semi-structured interviews, and documentation. Data analysis employed an interactive model encompassing data reduction, data presentation, and drawing conclusions using open coding, axial coding, and selective coding techniques. Data validity was tested through source triangulation, technique triangulation, and member checking to ensure the credibility of the research findings. The research results indicate that performance evaluation plays a strategic role in improving the quality of education by strengthening the professionalism of educators and educational support staff, developing human resources based on needs, and enhancing the quality of educational services. Performance evaluation serves not only as an assessment tool but also as a means of reflection and continuous improvement that fosters increased competence, discipline, and work responsibility. The evaluation results are utilized as the basis for developing more targeted coaching, training, and mentoring programs. These findings reinforce the perspectives of Performance Management, Human Capital Theory, and Total Quality Management, which hold that performance evaluation is an organizational development instrument that contributes to the continuous improvement of service quality and educational quality.